The Impact of Approved Accounting Standard AASB 1024 â€œConsolidated Accountsâ€ on the Information Included in Consolidated Financial Statements - Pramuka, Bambang Agus (The International Journal of Accounting and Business Society, 1995)
The intent of consolidated financial statements is to provide meaningful, relevant, useful, and reliable information about the operations of a group of companies. In compliance with AASB 1024 ’Consolidated Accounts’, and AAS 24 Consolidated Financial Reports’, a parent entity now has to include in its consolidated financial statements all controlled entities, regardless of their legal form or the ownership interest held. The new Standard also provides a new style of consolidated financial statements format, which requires an increased disclosure of outside equity interest (OEI, formerly minority interest), especially in the Balance Sheet. The purpose of this study is to determine the impact of AASB 1024 on the consolidated financial statements of effected companies. Examination of the financial statements of 52 companies reveals that: (1) the adoption of AASB 1024 (and AAS 24) did significantly alter the structure and format of the basic financial statements, especially the Balance Sheet in terms of disclosing the OEI; and (2) the adoption of AASB 1024 (and AAS 24) had no significant impact on the consolidated financial figures.